Moral Politics in the Digital Space: Dedi Mulyadi’s Populist Strategy in Building Leadership Image on Instagram - Jordy Jordy; Rino Dwi Putra; Nur Rani; Arista Damayanti (Iapa Proceedings Conference, 2025)
This study analyzes Kang Dedi Mulyadi’s (KDM) political branding strategy on Instagram as a manifestation of local moral populism. It argues that his leadership image is built on personal morality and Sundanese cultural values rather than policy rationality. Qualitative content analysis reveals a consistent prioritization of Political Value and Activity Report posts, positioning KDM as a simple, moral, and hard-working leader. This image is reinforced by focusing on Relationship and Personal Value in his personality content, which builds emotional closeness with the public. Visual elements, particularly white Sundanese traditional clothing, serve as symbolic markers of simplicity and local wisdom. KDM’s success creates a paradox: it effectively builds trust through affective bonds but risks shifting the political arena from rational deliberation to a personal moral stage, potentially weakening democratic accountability (the “Halo Effect”).